2017
DOI: 10.3390/nu9121366
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns in Relation to Metabolic Syndrome among Adults in Poland: A Cross-Sectional Study

Abstract: In several populations the associations between diet and the risk of metabolic syndrome have not been fully examined yet. The aim of the study is to identify the main dietary patterns among Polish adults and the evaluation of the relationships of these patterns with metabolic syndrome and its components. The study was conducted on a group of 7997 participants, aged between 37 and 66 years old. Dietary patterns were identified by factor analysis. Metabolic syndrome was defined according to the International Dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
55
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 54 publications
8
55
0
2
Order By: Relevance
“…In the current study, according to the IDF definition [ 5 ], we reported that prevalence of MetS was 38.2% in a randomly-selected sample of the Czech urban population, which is similar with that reported among Polish, neighboring Central European population [ 25 ]. The diagnosis of MetS was more common among male, low-educated, unemployed and smoking subjects.…”
Section: Discussionsupporting
confidence: 86%
“…In the current study, according to the IDF definition [ 5 ], we reported that prevalence of MetS was 38.2% in a randomly-selected sample of the Czech urban population, which is similar with that reported among Polish, neighboring Central European population [ 25 ]. The diagnosis of MetS was more common among male, low-educated, unemployed and smoking subjects.…”
Section: Discussionsupporting
confidence: 86%
“…Assim, estes achados demonstram que uma alimentação equilibrada e a adesão a uma vida fisicamente ativa são metas fundamentais para indivíduos com SM e constituem dois eixos fundamentais no processo de modificação do estilo de vida para a melhora dos fatores de risco modificáveis para DCV 22,26 . Estudos têm comprovado que o exercício físico possui um importante papel na manutenção da estrutura e função vascular 8 , e a inadequação alimentar já se mostrou impactar de forma significativamente negativa sobre mortalidade cardiovascular 8,24,27 .…”
Section: Conclusãounclassified
“…Particularly detrimental pattern linked to MS is being described as the 'western' pattern; defined by a high intake of red and processed meats, fast foods, refined grains, desserts, sweets [19]. The latter relationship is well documented in multiple studies [20][21][22] and confirmed in the recently published meta-analyses by Rodríguez-Monforte et al [23] and Shab-Bidar et al [24]. To our knowledge, no previous studies used two different approaches in assessing diet quality in the context of metabolic health in a group of young adults.…”
Section: Introductionmentioning
confidence: 99%